Microbiomes of the Amazon forest: bacterial diversity and community structure in the phyllosphere, litter and soil - Moreira, Julio Cezar Fornazier (2019)
Forest biomes cover approximately 38 million km2 worldwide, from which one third represent tropical and subtropical forests. Among these biomes, the Amazon forest is one of the most important for its roles in global climate regulation and dueling high levels of plant, animal and microbial diversity. The Amazon forest represents 60% of Brazilian territory and has been constantly threatened by the expansion of agricultural and animal husbandry areas. The reduction of the biodiversity levels in the Amazon may result in unforeseen impacts on the stability of the biome. The role of the microorganisms in this process is unknown. In general, the knowledge about the microbial diversity and community structure in the Amazon forest, as well the drivers of these community are poorly understood. It has been observed in the Brazilian Atlantic forest that the bacterial communities associated to the phyllosphere, dermosphere and rhizosphere of several tree species are unique and depend on the plant taxon. In order to unravel the drivers of the bacterial communities associated to plants of the Amazon forest in specific microenvironments, we evaluated the bacterial communities associated with the phyllosphere, litter and rhizospheric soil of nine tree species at three time points in a pristine Amazon forest in Brazil, using high-throughput sequencing of 16S rRNA genes. Our results showed that bacterial alpha diversity in the rhizosphere is higher than in the phyllosphere. However, the phyllosphere showed higher levels of heterogeneity (i.e. higher beta diversity). We also observed that an extreme drought during the ENSO 2015-2016 affected mainly the phyllosphere bacterial communities, inducing decreases in alpha diversity and increases in beta diversity. Our results also showed that plant species and plant functional traits are important drivers of the bacterial communities in the Amazon forest. In general, our data indicate that even though plant species is an important determinant of phyllosphere, litter and rhizospheric soil bacterial community structures, extreme climatic events (such as drought) may induce significant changes in bacterial diversity and community structure of the Amazon forest trees, with possible changes in functionality.